The efficient combination of taxes on fuel and vehicles - Geir H. M. Bjertnæs (Statistics Norway, Research Department, 2017)
A tax on fuel combined with tax-exemptions or subsidies for purchase of fuel-efficient vehicles is implemented in many countries to reduce greenhouse gas emissions and other negative externalities from road traffic. This study, however, shows that a tax on fuel should be combined with heavier taxation of fuel-efficient vehicles to curb externalities from road traffic. The tax on fuel is implemented to curb externalities linked to both consumption of fuel and road use. The heavier tax on fuel-efficient vehicles prevents that motorists avoid the road user charge on fuel by purchasing fuel-efficient vehicles.
Keywords: H2; H21; H23; Q58; R48; 330; Transportation; optimal taxation; environmental taxation; global warming